Interest Rate Movements and Inflation Risk in the Philippines - Dela Cruz, Alma; Dickinson, David (Philippine Management Review; Vol 18 (2011), 2011)
This article examines the role of inflation risk in the determination of interest rate movements in the Philippines. The analysis proceeds by first estimating a measure of inflation risk that is analytically derived from the consumption-based capital asset pricing model (CCAPM). This inflation risk measure, the covariance of purchasing power growth and consumption growth, is estimated using a multivariate GARCH method on quarterly Philippine data from 1986 to 2005. The estimated inflation risk series is then used in a CCAPM-based interest rate model to help explain interest rate movements in the Philippines.
Keywords: inflation risk; multivariate BEKK-Garch; CCAPM